Development of Interactive Media Articulate Storyline Loaded with Local Wisdom to Enhance Understanding of Main Ideas in Elementary Schools - Misie Aditiyarini; Nugraheti Sismulyasih SB (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to develop interactive media Articulate Storyline loaded with local wisdom to enhance students' understanding of main ideas. The research model used is the research and development model by Sugiyono. This research was conducted at SDN Ngaliyan 03 and SDN Ngaliyan 05 in Semarang City, Central Java, with 6 students as samples for limited testing and 26 students for usability testing. The research instruments used include test and non-test techniques such as questionnaires, interviews, pretests and posttests, as well as documentation. This research employs both qualitative and quantitative data analysis methods. The technique for qualitative data analysis involves suggestions and feedback from media or material experts. Meanwhile, the quantitative data analysis uses parametric data analysis techniques such as normality tests, t-tests, and N-Gain tests. The research results show that the validation of material feasibility received a score of 88% and media experts 82%. Thus, the interactive media Articulate Storyline loaded with local wisdom is declared very feasible. In addition, the average improvement in pretest and posttest results shows an increase of 43.23. This means there is a difference before and after using the interactive media Articulate Storyline loaded with local wisdom. The N-Gain percent test results show a percentage of 76.83%. Research findings indicate that the use of interactive media Articulate Storyline combined with local wisdom is highly feasible and effective in enhancing students' understanding of the main idea.